Non-dioxin-like polychlorinated biphenyls induce a release of arachidonic acid in liver epithelial cells: a partial role of cytosolic phospholipase A(2) and extracellular signal-regulated kinases 1/2 signalling - Umannová, L; Neca, J; Andrysík, Z; Vondrácek, J; Upham, B L; Trosko, J E; Hofmanová, J; Kozubík, A; Machala, M (Toxicology, 2008)
Non-dioxin-like polychlorinated biphenyls (NDL-PCBs) have been shown to act as tumor promoters in liver; however, the exact mechanisms of their action are still only partially understood. One of the interesting effects of NDL-PCBs is the acute inhibition of gap junctional intercellular communication (GJIC), an effect, which has been often found to be associated with tumor promotion. As previous studies have suggested that NDL-PCB-induced disruption of lipid signalling pathways might correspond with GJIC inhibition, we investigated effects of PCBs on the release of arachidonic acid (AA) in the rat liver epithelial WB-F344 cell line, a well-established model of liver progenitor cells. We found that both 2,2',4,4'-tetrachlorobiphenyl (PCB 47) and 2,2',4,4',5,5'-hexachlorobiphenyl (PCB 153), but not the dioxin-like, non-ortho-substituted, 3,3',4,4',5-pentachlorobiphenyl (PCB 126), induce a massive release of AA. The AA release, induced by PCB 153, was partially inhibited by extracellular signal-regulated kinases 1/2 (ERK1/2) signalling inhibitor, U0126, and by cytosolic phospholipase A(2) (cPLA(2)) inhibitor, AACOCF(3). Although PCB 153 induced both ERK1/2 and p38 activation, the specific p38 kinase inhibitor, SB203580, had no effect on AA release. Inhibitors of other phospholipases, including phosphatidylcholine-specific phospholipase C or phosphatidylinositol-specific phospholipase C, were also without effect. Taken together, our findings suggest that the AA release, induced by non-dioxin-like PCBs in liver progenitor cell line, is partially mediated by cytosolic PLA(2) and regulated by ERK1/2 kinases. Our results suggest that more attention should be paid to cell signalling pathways regulated by AA or eicosanoids after PCB exposure, which might be involved in their toxic effects.
Keywords: kmenové buňky; epitelové buňky; buněčné linie; Rats, Inbred F344; Cell Line; cytosolické fosfolipasy A2; zvířata; Liver; mitogenem aktivovaná proteinkinasa 3; Signal Transduction; Phospholipases A2, Cytosolic; Arachidonic Acid; Stem Cells; signální transdukce; polychlorované bifenyly; Animals; potkani inbrední F344; kyselina arachidonová; mitogenem aktivovaná proteinkinasa 1; krysa rodu Rattus; Epithelial Cells; Environmental Pollutants; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 1; Rats; látky znečišťující životní prostředí; játra; Polychlorinated Biphenyls